PENGARUH FASILITAS KERJA, PELATIHAN DAN LOYALITAS TERHADAP PRODUKTIVITAS KERJA GURU SMP AL-AZHAR MEDAN - Wansah, Aldi; Aginta, Windy; Bahri, Syamsul (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2024)
The purpose of this study is to determine the Effect of Work Facilities, Training and loyalty on the Work Productivity of Al-Azhar Medan Junior High School Teachers. The research sample consisted of 57 teachers of Al-Azhar Medan Junior High School, and the data used was raw data. This study analyzes the effect of work facilities, training, and loyalty on teacher productivity using multiple linear regression statistical methods (multiple regression analysis) and qualitative methods using instrumental data testing, classical hypothesis testing, and hypothesis testing. The results showed that work facilities (X1), training (X2), and loyalty (X3) partially had a positive and significant effect on teacher work productivity (Y). The work facility (X1) has a calculated t value of 9.832 and a significance level value of 0.000. Training (X2) has a calculated t value of 6.077 and a significance level value of 0.000. Loyalty (X3) has a calculated t value of 4.449 and a significance level value of 0.018. Simultaneously, work facilities (X1), training (X2), and loyalty (X3) have a positive and significant effect on the work productivity of Al-Azhar Medan Junior High School teachers with a calculated F value of 49,708 and a significance level value of 0,000. The coefficient of determination (R2) is 0.959 (95.9%).